Analisis Penerapan Sangfor Ngaf Firewall Sebagai Keamanan Pada Jaringan Internet Universitas Muhammadiyah Purwokerto - Yusril Amru; Ermadi Satriya Wijaya (Jurnal Sistem Informasi (JUSIN), 2022)
Computer network technology is developing very rapidly, but as a result of these technologicaldevelopments causing the exploitation of security gaps in network systems by exploiting securitholes, unauthorized users can easily commit crimes in the cyber world known as Cyber CrimeSniffing, Spoffing, DoS attacks. Sangfor NGAF is a network firewall security tool designed to filteand check across networks and applications, The analysis is intended to provide an overview ofsecurity vulnerabilities in network systems where these steps are important steps to determine thebest way to close security holes in the network. In this analysis there are steps taken, namelPreparation, Observation, Data Collection, and Network Analysis. The results of this study areseveral servers that have been compromised, from the analysis results obtained there are variouskinds of attacks including WebShell or Backlink, Bot Controlled, Brute-force, SQL Injection, and so on.